"Delayed Villous Maturation" in Placental Reporting: Concordance among Consultant Pediatric Pathologists at a Single Specialist Center. (September 2015) - Al-Adnani, Mudher; Marnerides, Andreas; George, Simi; Nasir, Alia; Weber, Martin A.
Delayed villous maturation (DVM) has been associated with an increased risk of adverse pregnancy outcome, including stillbirth, in the late third trimester, but there are limited published data. Moreover, it is recognized that the assessment of villous maturation is subjective and hampered by both intraobserver and interobserver variability. This audit aims to assess concordance in the reporting of DVM among pediatric pathologists at a single specialist center to improve reproducibility of this potentially important diagnosis. This is a retrospective review of singleton placentas from pregnancies at 35 weeks gestation or greater submitted for histopathologic examination between June 2013 and December 2013. Placental slides were reviewed independently by 4 pediatric pathologists, blinded to the original report, apart from gestational age; villous maturation was assessed as appropriate, accelerated, or delayed for the stated gestational age. A total of 464 placental histopathology reports were reviewed, of which 164 were greater than 35 weeks gestation; of those, 42 (26%) were originally reported as DVM. Following the audit slide review, 38 cases (23%) were assessed to show DVM by at least 1 pathologist. Consensus, with at least 3 pathologists agreeing to a diagnosis of DVM, was achieved in only 14 cases (9% of all cases reviewed; 37% of all cases called DVM). However, the proportion of overall agreement between 2 of the pathologists was 0.92. Concordance for DVM is poor among pathologists and subject to much interobserver variability. Consistency may be improved by consensus histologic review of all the placentas in which the diagnosis of DVM is being considered and stringent application of the published diagnostic criteria.